Design and development of a manually operated oil palm crusher - Islam, MR; Awal, MA; Mistry, CK (Progressive Agriculture, 2021)
Palm growers in Bangladesh are currently facing problems to extract crude palm oil from FFB. The traditional method of palm oil processing is time-consuming, laborious, hazardous, and inefficient resulting in the production of low-quality oil. Though mechanical processing is costly but produces good quality Crude Palm Oil (CPO) and the oil recovery rate is high. A low-cost mechanical (manually operated) oil palm crusher was designed and febricated in the workshop of the Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh. The crusher was designed by using Auto-Cad software. It was fabricated according to design parameters. It is fabricated by stainless steel (SS) shaft, stainless steel cylinder, mild steel (MS) hopper, (MS) hollow bars, MS pressure case cap & Bearing. It requires a very small rotating force. The cost of the crusher is only BDT 12000, which is within the buying capacity of the farmers of Bangladesh. Crusher was mounted on the table or bench. At first 500 gm fresh palm fruits were taken for experimentation. About 300 gm mesocarp and 200 gm oil palm kernel (nuts) were found from 500 gm oil palm fruits. Heating 300 gm mesocarp about 15 minutes and was weighted 280 gm mesocarp due to moisture loss. About 62 gm crude palm oil, 124 gm oil cake, 88 gm skum were collected from 280 gm mesocarp. The average m.c (wb) of fresh palm fruit was found 20.73%. The crushing capacity of the mesocarp of the crusher was o.84 kg/hr. The rotating speed of the screw was 26 rpm. Crude oil percentage was found 22.14%. The total time to extract 62 gm crude palm oil from 500 gm of fresh fruit was 1hr and 15 minutes. The weight of the crusher is 11 kg which is easy to operate by one man. The overall performance of the crusher was found quite satisfactory and could be useful for smallholder palm growers in Bangladesh. Progressive Agriculture 32 (1): 60-70, 2021